2015
DOI: 10.1128/jcm.01963-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clinical Aeromonas Species by rpoB and gyrB Sequencing and Development of a Multiplex PCR Method for Detection of Aeromonas hydrophila, A. caviae, A. veronii, and A. media

Abstract: Conventional identification of Aeromonas species based on biochemical methods is challenged by the heterogeneous nature of the species. Here, we present a new multiplex PCR method directed toward the gyrB and rpoB genes that identifies four Aeromonas species, A. hydrophila, A. media, A. veronii, and A. caviae, and we describe the application of this method on a Danish strain collection.A eromonas spp. are highly adapted to aquatic environments and have been described as pathogenic to humans and animals. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 21 publications
2
35
0
1
Order By: Relevance
“…For 16S rRNA gene sequence, bacterial culture was sent to the genomic division of Macrogen (Korea) where nucleotide sequencing reaction was performed by using ABI PRISM 3730XL Analyzer with BigDye (R) Terminator v3.1 Cycle Sequencing Kits (Applied Biosystems, USA). For accurate identification of the pathogen, species-specific multiplex PCR assay was performed [9]. After the preforming the Vitek System2 analysis, the result indicated that the isolated bacteria as A. hydrophila or Aeromonas caviae.…”
mentioning
confidence: 99%
“…For 16S rRNA gene sequence, bacterial culture was sent to the genomic division of Macrogen (Korea) where nucleotide sequencing reaction was performed by using ABI PRISM 3730XL Analyzer with BigDye (R) Terminator v3.1 Cycle Sequencing Kits (Applied Biosystems, USA). For accurate identification of the pathogen, species-specific multiplex PCR assay was performed [9]. After the preforming the Vitek System2 analysis, the result indicated that the isolated bacteria as A. hydrophila or Aeromonas caviae.…”
mentioning
confidence: 99%
“…; Persson et al . ). However, cross‐amplification reactions may result in incorrect identification of resistance genes.…”
Section: Resultsmentioning
confidence: 97%
“…Analyses using housekeeping genes, known as the gold standard for Aeromonas species identification, can determine base differences in the genome, and a number of Aeromonas species have been reclassified and new species identified as a result of their use, especially over the last decade (Beaz‐Hidalgo et al., ; Janda & Abbott, ; Martínez‐Murcia et al., ). Most researchers have reported that Aeromonas species should be analysed phylogenetically to determine intraspecific differences that can aid in the sequencing of housekeeping genes such as gyr B, rpo D or a combination (Beaz‐Hidalgo et al., ; Martínez‐Murcia et al., ; Persson, Al‐Shuweli, Yapici, Jensen, & Olsen, ; Soler et al., ). Janda and Abbott () determined that A. tecta and A. aquariorum (first identified in 2008) are affiliated with A. encheleia and that A. caviae , A. media and A. molluscorum (first identified in 2007) are affiliated with A. bivalvium .…”
Section: Discussionmentioning
confidence: 99%